Factors Associated with Clients’ Satisfaction on Hospital Service Management of Province 1, Eastern Nepal - Niraula, Tika Prasad; Poudel, Santosh Raj (Nepal Journal of Multidisciplinary Research, 2019)
Satisfaction is both the internal happiness and sadness which is the major result of the correlation between the desires and expectations of people and also the services received. The direct relation is with the health services provided to the people which are effectively used where the fulfillment of patient is always kept on the list of high priority. This satisfaction of people directly links with the major factors like healthy communication with the staffs of hospitals like doctors, nurses and other personnel, nature of quality services and other facilities provided by the hospital. The study of this is the descriptive and huge study which is currently carried out in province 1 of the eastern Nepal in 10 hospitals in different locations. Based on the random sampling, the hospitals were selected from the province 1 which resulted in 18 government hospitals and 40 private hospitals which are running currently. Among the 18 government hospitals, 6 government hospitals and 40 private hospitals, 4 private hospitals were chosen at random using the simple random sampling method. Client’s perspective and service provider’s perspective are the two perspectives which is the result of both the qualitative and the quantitative analysis. The results of both bivariate and multivariate analysis for the statistical significance of quantitative data have been presented which mainly focuses on the group discussion of it that is also reported. A survey was conducted which mainly involved the patients. The majority of patients were satisfied with the number of doctors available and the result of the diagnosis which ranged from 70.88% to 92.5% of the participants. However, there were patients; almost 30% who were not satisfied for longer period to visit doctors, 26.4% of clients were dissatisfied for the approach of doctors specialist in time.